Additive bases via Fourier analysis. (29th November 2021) - Arsovski, Bodan
Abstract: Extending a result by Alon, Linial, and Meshulam to abelian groups, we prove that if G is a finite abelian group of exponent m and S is a sequence of elements of G such that any subsequence of S consisting of at least $$|S| - m\ln |G|$$ elements generates G, then S is an additive basis of G . We also prove that the additive span of any l generating sets of G contains a coset of a subgroup of size at least $$|G{|^{1 - c{ \in ^l}}}$$ for certain c = c ( m ) and $$ \in = \in (m) < 1$$ ; we use the probabilistic method to give sharper values of c ( m ) and $$ \in (m)$$ in the case when G is a vector space; and we give new proofs of related known results.